1989
DOI: 10.1007/bf00378959
|View full text |Cite
|
Sign up to set email alerts
|

Resource partitioning between shrubs and grasses in the Patagonian steppe

Abstract: Experiments were conducted in the Patagonian steppe in southern South America to test the following hypotheses: (a) grasses take up most of the water from the upper layers of the soil and utilize frequent and short-duration pulses of water availability; (b) shrubs, on the contrary, take up most of the water from the lower layers of the soil and utilize infrequent and long-duration pulses of water availability. Grasses and shrubs were removed selectively and the performance of plants and the availability of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
302
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(354 citation statements)
references
References 21 publications
26
302
0
7
Order By: Relevance
“…Resources used by plants supported the idea of niche complementarity. We found that plots with grasses, which in the Patagonian steppe are shallow-rooted in comparison with shrubs (22), decreased soil water content on the upper 20 cm of the soil profile in spring and at the end of the growing season (ANOVA: Oct 02, F 1,82 Ï­ 4.095, P Ïœ 0.05; May 03, F 1,82 Ï­ 3.620, P Ïœ 0.061) (SI Fig. 6).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Resources used by plants supported the idea of niche complementarity. We found that plots with grasses, which in the Patagonian steppe are shallow-rooted in comparison with shrubs (22), decreased soil water content on the upper 20 cm of the soil profile in spring and at the end of the growing season (ANOVA: Oct 02, F 1,82 Ï­ 4.095, P Ïœ 0.05; May 03, F 1,82 Ï­ 3.620, P Ïœ 0.061) (SI Fig. 6).…”
mentioning
confidence: 75%
“…In the Patagonian experiment, niche partitioning and positive interactions reflected long-term species coexistence. Grasses and shrubs in the steppe showed extensive niche partitioning for soil water use with depth (22,24). Other differences are also very likely to occur, such as soil water use in time by species with different phenology, and differences in nutrient use in space and time (25).…”
mentioning
confidence: 99%
“…The vegetation is classified as semiarid steppe, with the dominant life forms of perennial tussock grasses and shrubs, which account for . 95% of the aboveground biomass of this community (Sala et al, 1989;Golluscio and Sala, 1993). Vegetative cover is discontinuous, with cover of 25% by grass species and 12% by shrub species (FernĂĄndez et al, 1991).…”
Section: Study Areamentioning
confidence: 98%
“…Ecosystem processes in semi-arid ecosystems such as those located in the Patagonian region of Argentina, are primarily limited by water availability (Sala et al, 1989;JobbĂĄgy and Sala, 2000). The Patagonian steppe is codominated by shrubs and grasses on a matrix of bare soil.…”
Section: Introductionmentioning
confidence: 99%
“…Models based on the 'Walter hypothesis' -4-have been widely applied in literature (Walker et al, 1981, Walker and Noy-Meir, 1982, Eagleson and Segarra, 1985, van Langevelde et al, 2003. Some experiments and observations have supported 'Walter hypothesis' (Knoop and Walker, 1985, Sala et al, 1989, Pelaez et al, 1994 but many others have cast doubts on the existence of vertical rooting niche separation (Scholes and Walker, 1993, Belsky, 1990, Le Roux et al, 1995, Mordelet et al, 1997, Smit and Rethman, 2000, Hipondoka et al, 2003.…”
Section: What Is Special About the Savanna Environment That Allows Trmentioning
confidence: 99%